Seed Mycoflora in Kidney Bean (Phaseolus vulgaris L.) in Himachal Pradesh - DEEPIKA SUD; O.P. SHARMA; P.N. SHARMA (Seed Research, 2026)
Investigations on comparative occurrence of mycoflora on vegetable and pulse type of beans revealed that vegetable type varieties harboured more mycoflora as compared to pulse type beans. Agar plating of seeds showed the presence of 16 species of pathogenic and storage fungi belonging to ten genera. However, the frequency of fungi was more on unsterilized seeds (4.0-64.0%) as compared to sterilized seeds (8.0-32.0%) in both types of beans. Major storage and pathogenic fungi recorded were the species of Alternaria, Aspergillus, Cladosporium, Colletotrichum, Fusarium, Penicillium, Rhizoctonia, Rhizopus, Stemphylium and Trichoderma. Presence of mycoflora on seed had little effect on seed germination; however, higher germination was recorded in surface sterilized seeds of both types of beans. Seed smearing with fungal spore suspension revealed that almost all the storage fungi except Cladosporium sp. had least effect on seed germination. However, culture filtrates of these fungi reduced the germination drastically along with induction of variable symptoms.